Citrulline and intestinal fatty acid-binding protein as biomarkers for gastrointestinal dysfunction in the critically ill - Annika Blaser; Martin Padar; Jonathan Tang; John Dutton; Alastair Forbes (Anaesthesiology Intensive Therapy, 2019)
Currently there is no reliable tool available to monitor gastrointestinal function in the critically ill. Biomarkers are therefore of great interest in this field as the lack of monitoring tools impedes any interventional studies. The potential biomarkers citrulline and intestinal fatty acid-binding protein (I-FABP) are the present focus. Targeted literature searches were undertaken for physiology and pathophysiology, sampling, measurement methods and clinical use of citrulline and I-FABP as biomarkers of intestinal function and injury. Physiology and pathophysiology, specific aspects of sampling and different laboratory assays are summarized and respective pitfalls outlined. Studies in animals and patients outside the ICU support the rationale for these biomarkers. At the same time, evidence in critically ill patients is not yet convincing, several specific aspects need to be clarified, and methodology and interpretation to be refined. We conclude that there are good physiological rationales for citrulline as a marker of enterocyte function and for I-FABP as a marker of intestinal injury, but further studies are needed to clarify whether and how they could be used in daily practice in caring for critically ill patients.